Semite influence on Viktor Frankl's anthropological vision - Flores Morales, Jorge Alberto (2020)
The present paper provides a reflection on the Semitic influence on Viktor Frankl regarding the vision of man in his physical, psychic and spiritual dimensions. An influence, little referenced in connection with philosophy as epistemological support of psychology, which will contribute to the proposal of the ontological three-dimensionality of man and will alert us to any anthropological reductionism that regards man as only the product of unconscious forces or behavioral neurochemicals expressions